The Use of Taxonomy to Update the Value of Bank Mortgage Collateral for Residential Real Estate – the Example of Wroclaw - Bywalec, Magdalena; Makowska, Anita (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The Polish Financial Supervision Authority̛s regulations on credit risk management in bank portfolios require banks to update the value of real estate that provides collateral for mortgages. Using statistical analysis to determine the value of real estate on the Polish market, scientists and market practitioners are working on other methods of determining the value of real estate, as specified in the Regulation of the Council of Ministers of 21 September 2004 on the Real Estate Valuation and Appraisal Report.The paper explains the uses and consequences of taxonomy to update the value of mortgage collateral in banks. It presents a comparison of a traditional real estate valuation method, paired comparison, with the effects of the valuation of the taxonomic method pattern.  As a result of updating the value of residential property portfolios held by banks, done at the end of 2016, there were 50 valuations corrected in minus and 47 in plus. Updating the value of the real estate portfolio using based on taxonomic analysis indicated 29 corrections in minus and 68 corrections in plus in variant I and 32 in minus and 65 in plus in variant II. There was a noticeable increase in value, which results in a higher value of the portfolio, which in variant I reached PLN 33 742 098.85 in variant II PLN 33 754 650.85. In both variants, the value of the real estate portfolio increased after the pattern update.